2015
DOI: 10.4037/ajcc2015153
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Parental Participation During Rounds in a Pediatric Cardiac Intensive Care Unit

Abstract: Background Inviting parents of sick children to participate during the rounding process may reduce parents’ anxiety and improve communication between the parents and the health care team. Objectives To increase the percentage of available parents invited to participate in morning rounds in a pediatric cardiothoracic intensive care unit (CTICU). Methods Invita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…The majority of parents who experienced FCR in a cardiac PICU felt their participation in rounds increased their understanding. 25 In sum, parents who experience FCR report increased participation, resulting in greater understanding about their child's condition and treatment plan, which is consistent across studies with and without a comparator.…”
Section: Parent-perceived Knowledgementioning
confidence: 53%
See 1 more Smart Citation
“…The majority of parents who experienced FCR in a cardiac PICU felt their participation in rounds increased their understanding. 25 In sum, parents who experience FCR report increased participation, resulting in greater understanding about their child's condition and treatment plan, which is consistent across studies with and without a comparator.…”
Section: Parent-perceived Knowledgementioning
confidence: 53%
“…For example, parents have benefited from being given a brochure along with a verbal explanation of FCR. 25 Hospitals may also include a magnet outside of rooms used to indicate family and patient preference for participating in rounds, which has been successfully implemented in other hospital interventions. 43 It is also important to better understand the role and preferences of pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Of the 26 remaining studies, 16 were deemed high quality 1,2,6,7,8,[10][11][12]14,18,[22][23][24][25][26][27][28] and 10 were considered good quality. 9,13,[15][16][17][19][20][21]26,29 Eight studies reported significant results related to increased communication, satisfaction, and compliance. 6,7,11,20,[22][23][24]28 In the examination of level of evidence, 16 articles were deemed to be level III, which includes nonexperimental studies, qualitative studies, and meta-synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…9,13,[15][16][17][19][20][21]26,29 Eight studies reported significant results related to increased communication, satisfaction, and compliance. 6,7,11,20,[22][23][24]28 In the examination of level of evidence, 16 articles were deemed to be level III, which includes nonexperimental studies, qualitative studies, and meta-synthesis. 7,9,10,12,[14][15][16][17][18][19][22][23][24][25]29,30 One study, a systematic review, was deemed to be level IV, which includes expert consensus in systematic reviews and clinical practice guidelines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation